Potassium fertilisation reduces radiocesium uptake by Japanese cypress seedlings grown in a stand contaminated by the Fukushima Daiichi nuclear accident. Issue 1 (December 2017) - Komatsu, Masabumi; Hirai, Keizo; Nagakura, Junko; Noguchi, Kyotaro
Abstract We analysed suppressive effects of potassium (K) fertilisation on radiocesium (137 Cs) uptake by hinoki cypress (Chamaecyparis obtusa ) seedlings from soils contaminated after the Fukushima Daiichi Nuclear Power Plant accident. Three-year-old seedlings were planted in a clear-cut forest (ca. 4 ha) during June–July 2014, and potassium chloride fertiliser (83 kg K ha−1 ) was applied twice (August 2014 and April 2015).137 Cs concentrations in the needles in the fertilised plots were one-eighth of those in the control (unfertilised) plots at the end of the second growing season (October 2015). Our results clearly indicated that K fertilisation reduced radiocesium transfer from soil to planted cypress seedlings. A linear mixed model analysis revealed that137 Cs concentrations in the needles were significantly affected by137 Cs inventory in the soil (Bq m−2 ) adjacent to the sampled seedlings, exchangeable K concentrations in surface mineral soils (0–5 cm) and fertilisation. The exchangeable K concentrations in surface soils in October 2015 did not differ from those in August 2014 (before fertilisation) in the fertilised plots and in the control plots. These results suggested that the levels of exchangeable K would temporarily increase by fertilisation during the growing season, and radiocesium uptake by tree roots was suppressed.